Radiological Characteristics of the Knee in Young Patients with Medial Meniscus Horizontal Tears - Naraoka, Takuya; Soneda, Hikaru; Hori, Runa; Morioka, So; Matsuyama, Yukihiro (The Journal of Knee Surgery, 2025)
We aimed to assess medial meniscal (MM) healing and horizontal tear (HT) repair in the knees of young patients.We enrolled 37 knees of 35 patients (mean age: 28.0 ± 10.2 years) with isolated meniscal repair that were divided into three groups: MM HT group (HT group, n = 15), MM tear except for HT group (MM group, n = 11), and lateral meniscus (LM) tear except for discoid meniscus group (LM group, n = 11). The anatomical lateral distal femoral angle (aLDFA), medial proximal tibial angle (MPTA), and posterior tibial slope were measured on preoperative radiographs. Magnetic resonance imaging was performed at 3, 6, and 12 months postsurgery. Clinical outcomes were evaluated using Lysholm and Knee Injury and Osteoarthritis Outcome Score (KOOS) at 24 months postsurgery.aLDFA values were significantly lower in the HT and MM groups than in the LM group (p = 0.007). The MPTA was significantly lower in the HT group than in the MM and LM groups (p = 0.000). There were no differences in meniscal healing among the three groups at any time point after surgery (p = 0.376, 0.830, and 0.523, respectively). The KOOS subscale scores, symptom, pain, sports and recreation, and quality of life in the HT group were significantly lower than those in the LM group (p = 0.021, 0.033, 0.035, and 0.041, respectively).Young patients with MM HT have small aLDFA and MPTA values. Although the healing rate of HT postrepair was comparable to other types of MM or LM tears up to 1 year postrepair, clinical outcomes (KOOS) of repaired HTs were inferior to those of LM tears 2 years postrepair.
Keywords: young patients; meniscus; horizontal tear; radiography; magnetic resonance imaging